Deglaciation of the northwestern White Mountains, New Hampshire - Thompson, Woodrow; Fowler, Brian; Dorion, Christopher (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1999)
Abstract The mode of deglaciation in the northwestern White Mountains of New Hampshire has been controversial since the mid 1800's. Early workers believed that active ice deposited the Bethlehem Moraine complex in the Ammonoosuc River basin during recession of the last ice sheet. In the 1930's this deglaciation model was replaced by the concept of widespread simultaneous stagnation and downwastage of Late Wisconsinan ice. The present authors reexamined the Bethlehem Moraine complex and support the original interpretation of a series of moraines deposited by active ice. We found other moraine clusters of similar age to the northeast in the Johns River and Israel River basins. Ice-marginal deposits that probably correlate with the Bethlehem Moraine also occur west of Littleton. The Bethlehem Moraine complex and equivalent deposits in adjacent areas were formed by readvance and oscillatory retreat of the Connecticut Valley lobe of the Laurentide Ice Sheet. This event is called the Littleton-Bethlehem Readvance. Throughout the study area, sequences of glaciolacustrine deposits and meltwater drainage channels indicate progressive northward recession of the glacier margin. Radiocarbon dates from nearby New England and Québec suggest that the ice sheet withdrew from this part of the White Mountains between about 12 500 and 12 000 14 C yr BP. We attribute the Littleton- Bethlehem Readvance to a brief climatic cooling during Older Dyas time, close to 12,000 BP.